The Relevance of Understanding Referencing Styles in the Era of Reference Managers - Goyal, Mohit; Goyal, Neha (Journal of Gastrointestinal Infections, 2022)
Writing the references of a manuscript accurately requires a significant amount of time and effort. While it can be a daunting task for beginners, even experienced authors can find it time consuming. The advent of reference managers brought a ray of hope of an end to this tedious toil. While these managers have eased the authors' task to a great extent, they may not always be completely accurate in the reference output they generate. Errors, inaccuracies, omissions, and compatibility issues do occur at times with the best of reference managers. It is thus of paramount importance to be able to recognize these issues and address them before submitting the manuscript to the journal. Sound knowledge of referencing styles helps in quick recognition and redressal of such errors thus increasing accuracy, ensuring consistency of references, and saving the author's time.
Keywords: citation; endnote; Harvard; limitation; manuscript; scientific writing; Vancouver; Zotero